Android-Based Learning Media for Vocational High School Students - Siregar, Bina Jaya; Ndruru, Liberlina; Tamba, Saut Parsaoran (International Journal of Natural Science and Engineering, 2021)
Online learning impacts decreasing student interest and learning outcomes, so students need media that can help the learning process. This research aims to produce an android-based learning application for vocational students. This research is classified as developed using the ADDIE model (analysis, design, development, implementation, and evaluation). The subjects involved in this study were two media experts, one teacher, and vocational students. Data collection in the study was carried out using the interview method and distributing questionnaires with an instrument in a product validity test questionnaire. The research data was analyzed using scores from each validator by adding up each score on each indicator and finally providing a valid assessment using the percentage assessment procedure. The study results indicate that the developed learning application media has a high validity score, so developing and teaching vocational high school students. In addition to having a high validity score, the learning application media has increased students' motivation and learning outcomes.